Challenges and potentialities of nursing work in street medical offices - Aline Costa Cardoso; Débora de Souza Santos; Silvana Martins Mishima; Danielly Santos Cardoso dos Anjos; Jorgina Sales Jorge; Hiule Perreira de Santana (Universidade de São Paulo, 2018)
ABSTRACT Objective: to analyze elements of the nursing work process in the Street Medical Offices, highlighting the challenges and potentialities of care for homeless people. Method: this is an exploratory research of qualitative nature supported by the perspective of the health work process. The study was conducted through semi-structured interviews with nurses from the teams of the street medical offices at the city of Maceió and data were analyzed according to the content analysis technique, approaching issues related to the object, instruments and purposes of the nursing work process. Results: the identified themes were: Need for health care in the context of social and health vulnerability; Strategic planning and teamwork as tools for organizing the work process; Purposes and products of work: guaranteeing the right to access and care. . Before a work object designed by serious health needs resulting from the social vulnerability of this population, nurses use different instruments in their work process: strategic planning, acting in multiprofessional team and valorization of the light technologies of reception and bonding. Conclusion: apart from the difficulties, the study presents a successful experience that explores the potentiality of sharing relationships of humanized care.